Le rôle des institutions culturelles et des missions à Ľ étranger dans la circulation des idées géographiques. Ľ exemple de la carrière de Pierre Deffontaines (1894-1978) - Delfosse, Claire (Finisterra, 1998)
THE PLACE OF CULTURAL POLICY ABROAD IN THE CIRCULATION OF GEOGRAPHICAL IDEAS: THE CASE OF THE CAREER OF PIERRE DEFFONTAINES (1894-1978). Between the two world wars, France reinforced its cultural policy abroad. Many French Institutes were founded, particularly in the coutries of the "Petit Entente" and in Latin America. These institutes were located near foreign universities which helped French Scholars travel abroad. Pierre Deffontaines (1894-1978) is significant in this respect, as most of his carrer took place abroad. Thanks to the two main successive positions which he held - one in France at the Catholic Faculties of Lille (1924-1939), the other in Spain as the director of the French Institute of Barcelona (1939-1964) - he travelled extensively abroad, particularly in the Americas: Brazil, Argentina, Uruguay and Québec. He may have been the French geographer who was the best known abroad and who promoted the largest number of geography departments and associations in various places. As a disciple of Jean Brunhes, he succeeded in associating the promotion of French culture to the promotion of geography.